Delayed Migration of a WallFlex Enteral Stent Resulting in Jejunal Perforation - Phillip S. Ge; Rabindra R. Watson; David C. Chen; V. Raman Muthusamy (Case Reports in Gastrointestinal Medicine)
Enteral stents are increasingly utilized to palliate malignant gastrointestinal obstruction; however, they can be associated with significant complications. We describe an unusual case of a 67-year-old male with gastric adenocarcinoma who underwent placement of a WallFlex metallic enteral stent to relieve a malignant gastric outlet obstruction. Four months later, while actively undergoing chemotherapy, he developed acute abdominal pain and was found to have delayed stent migration and jejunal perforation. He required emergent surgical resection of the perforated segment of jejunum. Delayed migration of the WallFlex enteral stent with subsequent visceral perforation has yet to be reported in the literature. Chemotherapy after stent placement has been associated with an increase in maintenance of stent patency; however, shrinkage of the local tumor by chemoradiation may increase the risk of stent migration. Care should be taken in placing enteral stents in patients undergoing continued treatment of their malignancy, as delayed migration of even uncovered stents may occur.